InGaN-LD-Pumped ${\rm Pr}^{3+}$ : ${\rm LiYF}_{4}$ Continuous-Wave Laser at 915 nm - Biao Qu; Bin Xu; Yongjie Cheng; Saiyu Luo; Huiying Xu; Yikun Bu; Patrice Camy; Jean-Louis Doualan; Richard Moncorge; Zhiping Cai (IEEE Photonics Journal, 2014)
We demonstrate the first InGaN-LD-pumped room temperature and continuous-wave laser operation of a Pr3+: LiYF4 crystal at 915 nm. A maximum output power up to 78 mW with a laser slope efficiency of about 17% is obtained. The round-trip optical losses are estimated to be about 0.45%, and the M2 beam quality factors measured in x and y dimensions are about 1.07 and 1.04, respectively.